IMPACT OF PIGEON PEA FLOUR, ISOMALTULOSE AND INULIN AS A SUBSTITUTE FOR WHEAT FLOUR, SUGAR AND FAT IN TOFFEE CAKE PRODUCTS - Sorndech, Waraporn; Ponklang, Wipaporn; Pumetum, Papawee; Lueachan, Rachata; Ploypetchara, Thongkorn; Budseekhot, Siriporn (Srinakharinwirot University Journal of Sciences and Technology, 2024)
Pigeon pea (Cajanus cajan) is a legume that is high in protein, low in fat, and contains higher amounts of several amino acids as compared to soybeans. In order to utilize pigeon pea in a healthy diet, the purpose of this research was to apply high-protein flour from pigeon pea to a healthy toffee cake product by substituting wheat flour. Moreover, the healthy ingredients for sugar and fat substitutes were added by using isomaltulose and inulin. The response surface method (RSM) experiment was planned, and the Box-Behnken experiment was designed in order to select the appropriate recipes for further analysis. Sensory evaluation of all toffee cake recipes showed that the toffee cake recipe with 4.0% (w/w) pigeon pea flour, 5.2% (w/w) isomaltulose, and 0.2% (w/w) inulin was highly accepted by the panelists (100% consumer acceptance). In addition, the appropriate toffee cake recipe, which was determined by the sensory and textural liking score, found that the suitable components of the toffee cake formula were 6.0% (w/w) pigeon pea flour, 5.2% (w/w) isomaltulose, and 0.5% (w/w) inulin. For toffee cake appearance and microstructure, which were determined by SEM, an increase in pigeon pea flour tends to change air pocket distribution and size of the toffee cake texture. The texture characteristics of the healthy toffee cake recipes showed that the hardness, gumminess, and chewiness were increased as compared to the control. The appropriate toffee cake recipe, which was determined by the sensory textural liking score (6.0% (w/w) pigeon pea flour, 5.2% (w/w) isomaltulose, and 0.5% (w/w) inulin), was chosen for nutritional analysis. The results showed that it contained 8.52 grams of protein per 100 grams. It also contains 34% less sugar than the control recipe (the healthy toffee cake formula has a total sugar content of 12.63 grams per 100 g). Hence, the healthy toffee cake formula containing pigeon pea flour obtained from this research can be further developed for commercial distribution.